Liver Biopsy - Attaya, Mohamed; Thabet, Ashraf (Digestive Disease Interventions, 2018)
Liver biopsies are among the most common procedures performed by the interventional radiologist. Liver biopsies may be performed through the percutaneous or transjugular approaches. Ultrasound, computed tomography (CT), or magnetic resonance imaging (MRI) may be used for imaging guidance. Transjugular liver biopsies are generally reserved for specific circumstances in which the percutaneous method is associated with increased risk to the patient, such as coagulopathy, or when portal pressure measurements are desired. In addition, endobiliary biopsy through percutaneous transhepatic tracts may be an important means of assessing biliary strictures when the endoscopic route is impossible. This article serves as a general review of the multiple diagnostic hepatic interventions that may be performed by the interventional radiologist.
Keywords: percutaneous liver biopsy; transjugular; biliary